Anti-angiogenic drugs for second-line treatment of NSCLC patients: just new pawns on the chessboard?. (2nd January 2016) - Bronte, Giuseppe; Passiglia, Francesco; Galvano, Antonio; Russo, Antonio
Abstract : Tumor angiogenesis is one of the main pathways targeted to treat cancer. Bevacizumab added survival benefit when combined with platinum-based chemotherapy in NSCLC. Recently, Phase III trials showed survival benefit when anti-angiogenic drugs are added to docetaxel as second-line treatment for NSCLC. These anti-angiogenic agents include nintedanib and ramucirumab, a tyrosine-kinase inhibitor and a monoclonal antibody, respectively, which target receptors involved in angiogenesis. These studies have some similarities and differences. We propose a new algorithm for treatment sequences in performance status 0-1 patients with non-oncogene-addicted NSCLC type adenocarcinoma. Indeed clearer scientific evidences are available for this subgroup of patients.